Hubungan Citra Diri dan Pola Asuh Orang Tua dengan Tingkat Kepercayaan Diri Pada Remaja Usia 17-19 Tahun - Nur Fatayatus Sholikhah; Moh. Saifudin; Abdul Rokhman (Jurnal Keperawatan Muhammadiyah, 2026)
Adolescence is a developmental phase marked by identity exploration and rapid physical and psychological changes. Self-confidenceplays a pivotal role during this period, as it enables adolescents to engage socially, achieve academically, and manage stress effectively. Self-confidence is influenced by both self-image and parenting style. This study aims to examine the relationship between self-image and parenting style with the level of self-confidence among adolescents aged 17- 19 at SMA Negeri 3 Lamongan. A quantitative approach with a cross-sectional design was employed, involving 187 student selected trough simple random sampling. Data were collected using the Coopersmith self-esteem inventory (to assess self-image), a parenting style questionnaire, and a Likert-scale-based instrument on self-confidence devepoment. Data were analyzed using Spearman’s Rank correlation test via SPSS 22. The results showed that the majority of student had a moderate self-image (62.6%) and moderate self-confidence (61.0%), while nearly all (91.4%) perceived their parents’ style as democratic. A significant relationship was found brtween self-image and self-confidence (r = 0.582, p = 0.000), and between parenting style and self-confidence (r = -0.166, p = 0.023). These findings highlight the importance of parenting approaches that support the development of a healthy self-image to foster optimal psychological growth in adolescents.